(untitled) (Applied Biological Research, 2024)
Urinary tract infections are an exceedingly common worldwide problem, caused mostly by Gram-negative bacteria, especially Escherichia coli. Microbial biofilms are considered a serious public health problem. The potential of uropathogenic E. coli (UPEC) to produce biofilm was explored in the present study. The Congo red agar, tube- and tissue culture plate methods were used to evaluate the formation of biofilm by E. coli isolates. Of the 155 isolates, 101, 106 and 90 isolates were positive for these three methods, respectively. Subsequently, the sensitivity of E. coli isolates to antimicrobial agents (amikacin, cefepime, cefixime, cefotaxime, cefpodoxime, ceftazidime, ceftriaxone, ciprofloxacin, nitrofurantoin, gentamycin, nalidixic acid, ofloxacin and pefloxacin) was tested. There was no difference in the rate of biofilm detection between Congo red agar method and tube method. The antibiotic sensitivity test revealed that the biofilm producing isolates were multi-drug resistant. The study emphasized the necessity for developing alternative therapeutic approaches to overcome multi drug resistance arising from biofilm formation of UPEC.